2015
DOI: 10.1007/s00784-015-1646-6
|View full text |Cite
|
Sign up to set email alerts
|

Can apical periodontitis affect serum levels of CRP, IL-2, and IL-6 as well as induce pathological changes in remote organs?

Abstract: AP may trigger a systemic immune response, impair remote organs, and affect the general health of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 38 publications
3
51
1
5
Order By: Relevance
“…A link between periodontitis and liver disease is best described in animal models, but clinical evidence is now also emerging . Akinkugbe et al recently reported that periodontitis was an independent risk factor for incident NAFLD, and Yoneda et al found that treatment of periodontitis led to reduction in serum transaminase levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A link between periodontitis and liver disease is best described in animal models, but clinical evidence is now also emerging . Akinkugbe et al recently reported that periodontitis was an independent risk factor for incident NAFLD, and Yoneda et al found that treatment of periodontitis led to reduction in serum transaminase levels.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis could affect the liver by several potential mechanisms. First, in periodontitis, oral bacteria and locally produced proinflammatory cytokines can enter the bloodstream and potentially induce liver damage . Secondly, oral bacteria such as Porphyromonas gingivalis can cause alterations in the gut microbiota, with subsequent decreased expression of tight‐junction proteins in the ileum and increased gut translocation and systemic inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that inflammatory diseases and infections may be the cause of and related to the emergence of cardiovascular problems . As an oral disease, AP is known to be a potential risk factor for cardiovascular diseases . Apical periodontitis and cardiovascular damage have complex etiologies and may have common general risk factors as well as pathogenic mechanisms.…”
mentioning
confidence: 99%
“…Previous animal studies on rats have demonstrated that AP affects blood homeostasis; it increases the serum levels of inflammatory mediators and thus can affect systemic health . Alterations in expression of inflammatory markers, such as creatine kinase (CK), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH), and in the activities of antioxidant enzymes, such as superoxide dismutase (SOD), have previously been studied in cardiovascular diseases and marginal periodontitis .…”
mentioning
confidence: 99%
See 1 more Smart Citation